A Socio-Semiotics Analysis of Names in Abejoye: A Yoruba Christian Video Film - Adekemi Agnes Taiwo; Adeoye Jelili Adewale (Britain International for Academic Research (BIAR-Publisher), 2023)
Naming is an integral part of Yorùbá culture. It has an identity effects on the bearers. It is also believed that names control the actions and conducts of the bearers. The Yorùbá film producers are always careful and conversant with the fact that names given to their character must reflect in their characterization because orúkọ ọmọ ní í ro ọmọ ‘name has effects on a child’. The script writer, Mike Bamiloye, uses the name to draw a sketch of the attitudes, behavior and stature of the characters. This study therefore interrogates the socio-semiotic interpretation of names given to selected characters in Yorùbá Christian film, Àbẹ̀joyè. It also examines the names given to individual character, family and town. The paper concludes that the Yorùbá philosophical beliefs in names reflect in the selected Christian movie despite the fact that Christianity abhors traditional beliefs; the cultural aspects cannot be underestimated. The film, Àbẹ̀joyè, which serves as our data source is produced by Mount Zion Film Productions, Nigeria and Flaming Sword Film Productions, Texas in 2020-2023. Bamiloye’s unique and stylish way of naming characters show his dexterity in Yorùbá literature which always portrays and projects her culture through the creative way of assigning name to characters. This study contributes to the existing body of knowledge on Yorùbá Christian film and names among Yorùbá people